PEMANFAATAN TEPUNG Azollasp PADA PAKAN IKAN NILA GIFT (Oreochromis sp.) - Kristin Aprilia; Siswarini Siswarini (Samakia : Jurnal Ilmu Perikanan, 2016)
Azolla sp. which has been regarded as a weed by farmers were able to put to good use. The utilization associated with protein content Azolla sp. is quite high, 24%. In addition digestibility value of these plants is also good. In this study tested the use of flour Azolla on tilapia fish feed gift with different percentages. The results of this study showed the best percentage Azolla sp. powder is 30% by value - average feed conversion ratio of 3.44% (P1) and 4.04% (P2) with the average value of the specific growth of 6.26%. This result indicates that the Azolla sp. flour can be used as an alternative feed ingredient in fish NilaGift (Orechromis sp.)